An assessment of the quality of reference service at the University of the Philippines Diliman Main Library - Sabat, Elizabeth Manalang 1952- (2000)
On the availability of collection, library users responded to how many books of their need were available during their search. Of the 383 respondents, 24 (7 percent) found all the books they wanted; 112 (29 percent) said that 4 out of 5 of the materials are available; 165 (43 percent) for 3 out of 5 of the books are available; 62 (16 percent) said 2 out of 5 books they were able to access; and 20 (5 percent) declared they located only 1 of the 5 books. The 3 out of 5 books option on the availability of collection gathered the highest number of respondents.